Developing Green Infrastructure for Baghdad City - Najeel Kamal AbdulRazzaq; Mayasa Farkad Abdul Raheem (Iraqi Journal of Architecture and Planning, 2018)
The public green spaces in Baghdad city have an obvious shortage and doesnâ€™t fulfill and meet the needs of the population and the required open space criteria, moreover these green spaces are disjointed, disconnected and does not function as a unified system, that is why it suffers from neglect which contributes to deterioration of the cityâ€™s environment and increasing air pollution.Human beings depended on nature into providing clean air and good health, with the growth of the population and the urban areas, there has been negative influence on the natural environmental system. A new term lately appeared â€œGreen Infrastructureâ€especially in the developed countries (USA, UK and other countries in Europe), as one form of solutions to conserve the natural environmental system of green and open spaces. Consequently this thesis depended on this new green space approach to solve the green spaces problem in Baghdad city and suggested new sites in different locations in the city to be a new green spaces connected to the existing green spaces in Baghdad. This will increase the public green space areas, accessibility to these areas and social cohesion, it will also contribute to the improvement of the cityâ€™s environment by reducing air pollution and reducing air temperature especially during the long summer season. Other economic benefits could be achieved by planning for a connected network of green spaces in Baghdad city as well.